Modulation of Relaxivity, Suspension Stability, and Biodistribution of Dendronized Iron Oxide Nanoparticles as a Function of the Organic Shell Design. (6th December 2014) - Walter, Aurélie; Parat, Audrey; Garofalo, Antonio; Laurent, Sophie; Elst, Luce Vander; Muller, Robert N.; Wu, Tao; Heuillard, Emilie; Robinet, Eric; Meyer, Florent; Felder‐Flesch, Delphine; Begin‐Colin, Sylvie
<x xml:space="preserve">Abstract</x> Nanoparticles (NPs) with a mean diameter of 10 nm are functionalized with three dendrons: D1 a PEGylated PAMAM dendron of generation 0.5, D2 a hydrophilic oligoethyleneglycol‐derivatized dendron (D2) displaying a phosphonic acid at the focal point, and D2–2P the same dendron than D2 but with two phosphonic acid anchoring agents. Their grafting is confirmed by IR spectroscopy and elemental analysis. All dendronized NPs are stable over a long period of time in suspensions in water and in different physiological media and display a mean hydrodynamic diameter smaller than 50 nm whatever the molecule architecture. NMRD profiles and relaxivity measurements highlight the influence of the molecule architecture on the water diffusion close to the magnetic core thus influencing the relaxation properties at low magnetic field. The high hydrophilic architecture of the dendron D2 by contrast to dendron D1 allows maintaining the colloidal stability in different conditions while ensuring a very good accessibility of water molecule close to the magnetic core. Coupling of a fluorescent dye on dendrons have allowed investigating the biodistribution of dendronized NPs, which are found to be quickly eliminated through urinary and hepatobiliary pathways within 4 h. Furthermore, no enhanced permeation and retention effect in tumors can be observed.